Corporate Social Responsibility and Family Economic Groups in Mexico - Pérez-Sánchez, Beatriz (2020)
In Mexico, the corporate social responsibility is an integral reference corporate practice in the global business, in the competition, the sufficient production and positive social and environmental results are expected in the national performance and company policies. Objective: To know which are the economic groups or large family companies that hold the distinctive of Socially Responsible Company accumulated until 2019. Materials and Methods: It is a documentary research, based on the review of the approaches of some authors in the field of research and especially public information: from company websites and the Mexican Center for Philanthropy (CEMEFI). The methods: historical, analytical and descriptive were used. Results: In 2019, there were 41 recent family economic groups that obtained the corporate social responsibility mark and were assumed to comply with global standards; global codes of practice, industry and association agreements that formulate sustainability policies in favor of Mexican society. Conclusion: The social responsibility as a concept defines a way of acting under ethical principles, aligning with sustainable development and appealing to the will of employers to innovate, produce without polluting and induce good practices in the company for the well-being of its employees and the environment.